Utilisation of isoelectric precipitation to recover fish protein isolate from seafood processing waste - Sasidharan, Abhilash; Michu, V. J.; Pradhan, Chiranjiv; Sabu, S. (Indian Journal of Fisheries, 2020)
Threadfin bream (Nemipterus japonicus) is an important marine fish species used in the preparation of surimi. The waste generated from surimi production contains large quantity of recoverable proteins, which could be utilised for byproduct development. In this study, Isoelectric precipitation (IEP) technique as a method to recover proteins from fish processing waste was attempted. The alkali aided IEP process extracted the fish protein isolate (FPI) efficiently with a yield of 84.13Â±0.11%. The highest protein yield was recorded at a homogenised sample to water ratio of 1:9. Maximum protein content was found at pH 13 with 19.63 Â±0.52% yield. FPI extracted had higher protein content, less ash and low lipid contents compared to the fish processing waste. The mean yield and protein composition of FPI extracted atdifferent treatments of pH and sample to water ratiowere found to be significantly different (p<0.05). Sample to water ratio of 1:9 and pH 13 was found to be the best combination among the different treatments attempted for FPI extraction from threadfin bream processing waste. Keywords: Fish Protein Isolate, Isoelectric precipitation, Seafood processing waste